Cutaneous hypersensitivity reactions to freshwater cyanobacteria – human volunteer studies - Stewart, Ian; Robertson, Ivan M; Webb, Penelope M; Schluter, Philip J; Shaw, Glen R (BMC dermatology, 2006)
Pruritic skin rashes associated with exposure to freshwater cyanobacteria are infrequently reported in the medical and scientific literature, mostly as anecdotal and case reports. Diagnostic dermatological investigations in humans are also infrequently described. We sought to conduct a pilot volunteer study to explore the potential for cyanobacteria to elicit hypersensitivity reactions. A consecutive series of adult patients presenting for diagnostic skin patch testing at a hospital outpatient clinic were invited to participate. A convenience sample of volunteers matched for age and sex was also enrolled. Patches containing aqueous suspensions of various cyanobacteria at three concentrations were applied for 48 hours; dermatological assessment was made 48 hours and 96 hours after application. 20 outpatients and 19 reference subjects were recruited into the study. A single outpatient produced unequivocal reactions to several cyanobacteria suspensions; this subject was also the only one of the outpatient group with a diagnosis of atopic dermatitis. No subjects in the reference group developed clinically detectable skin reactions to cyanobacteria. This preliminary clinical study demonstrates that hypersensitivity reactions to cyanobacteria appear to be infrequent in both the general and dermatological outpatient populations. As cyanobacteria are widely distributed in aquatic environments, a better appreciation of risk factors, particularly with respect to allergic predisposition, may help to refine health advice given to people engaging in recreational activities where nuisance cyanobacteria are a problem.